2017
DOI: 10.2147/ijn.s125192
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of tumor targeting with riboflavin-functionalized theranostic nanocarriers

Abstract: Photoacoustic imaging is an emerging method in the molecular imaging field, providing high spatiotemporal resolution and sufficient imaging depths for many clinical applications. Therefore, the aim of this study was to use photoacoustic imaging as a tool to evaluate a riboflavin (RF)-based targeted nanoplatform. RF is internalized by the cells through a specific pathway, and its derivatives were recently shown as promising tumor-targeting vectors for the drug delivery systems. Here, the RF amphiphile synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…39 First, 300 mL liposome-PEG-MnO nanocomplex (4 mM Mn) was injected via tail-vein into the BALB/c mice. Then, 10 mL peripheral blood was collected from the tail vein at different time points (5,15,30,45,60,120,180,240,360, 720 and 1440 minutes). The obtained blood was mixed with heparin sodium (90 mL) in separate tubes and digested with HNO 3 for Mn concentration determination by ICP-MS.…”
Section: Determination Of Blood Circulation Half-life Of Liposome-pegmentioning
confidence: 99%
See 1 more Smart Citation
“…39 First, 300 mL liposome-PEG-MnO nanocomplex (4 mM Mn) was injected via tail-vein into the BALB/c mice. Then, 10 mL peripheral blood was collected from the tail vein at different time points (5,15,30,45,60,120,180,240,360, 720 and 1440 minutes). The obtained blood was mixed with heparin sodium (90 mL) in separate tubes and digested with HNO 3 for Mn concentration determination by ICP-MS.…”
Section: Determination Of Blood Circulation Half-life Of Liposome-pegmentioning
confidence: 99%
“…[4][5][6][7] Except for the use as a drug delivery carrier, theranostic liposomes have been concerned more and more in recent years due to the demand of the simultaneous diagnosis and therapy. Such theranostic liposomes are commonly obtained by the co-encapsulation of drugs and imaging molecules, such as uorescent quantum dots, 8,9 magnetic resonance imaging contrast agents (MRI CAs), [10][11][12][13] CT imaging contrast agents, 14 photoacoustic imaging CAs, 15 and ultrasound imaging CAs. 16 Among them, MRI-based theranostic liposomes own special advantages, because MRI is a widely used non-invasive medical imaging technique in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the in vitro gel experiment of PA imaging, spectra of the NPs within the NIR region were analyzed by the PA-imaging system. The PA signal peaked at 800 nm ( Figure S2), due to the excellent absorption of ICG, 41 which was selected as the excitation NIR wavelength in the following experiments. As shown in Figure 2D and E, the PA signal strengthened linearly with increased concentration of FA-PEG-PLGA-Ptx@ICG-Pfh NPs from 2 to 10 mg/mL.…”
Section: Drug Loading and Laser-triggered Drug Releasementioning
confidence: 99%
“…ICG-encapsulated nanoparticles have been explored as an option to overcome these limitations. However, one report stated that that PA signal from ICG liposome was clearly resolved to a depth of 10 mm using chicken breast muscle [29], which is not appropriate for IPN localization. Our phantom study demonstrated that the PA signal increased logarithmically without a…”
Section: Plos Onementioning
confidence: 99%